Should we perform coronary artery revascularization without aortic manipulation more often? - Pawlaczyk, Rafał; Szyndler, Krzysztof; Lango, Romuald; Jagielak, Dariusz; Łoś, Andrzej; Woś, Łukasz; Bojar, Paweł; Rogowski, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction : The number of coronary artery surgery is decreasing since interventional cardiologists started to capture more and more patients for angioplasty procedures. One of their arguments to choose this treatment is higher probability of stroke after surgery. Our strategy is aimed to reduce neurological complications related to coronary artery surgery by performing the “no-touch aorta off-pump” procedure. Aim of the study : Retrospective analysis of influence of different surgical techniques on neuro-psychiatric complications and hospital mortality. Material and methods : A total of 693 consecutive patients operated for isolated coronary artery disease in 2009. The early results were analyzed in three groups: group A – “on-pump” surgery (61 cases); group B – “off-pump” surgery with the use of side clamping (499 cases); and group C – “no-touch aorta off-pump” surgery (133 cases). Results : During the early postoperative period 11 patients died (1.6%), including 4 from group A (6.5%), 7 from group B (1.4%) and none from group C (p = 0.0026). We reported 6 new focal neurological deficits, one from group A (1.6%), 4 from group B (0.8%), and one from group C (0.7%) (p = 0.79). Postoperative delirium was present in 41 patients, including 5 from group A (8.1%), 32 from group B (6.4%), and 4 from group C (3.0%) (p = 0.25). Conclusions : Anaortic coronary artery bypass is a safe procedure. The association between the degree of aortic manipulation and number of neuro-psychiatric complications has not reached statistical significance in our material